THE EDUCATIONAL INSTITUTIONS AND THE IMPORTANCE OF FAMILY FOR THE SOCIETY THAT THINKS, AND PRODUCES SOLUTIONS (PALIMPSEST / ПАЛИМПСЕСТ, 2020)
While determining the educational goals of our children during the school period, it is not possible to think of the child alone, the child is a whole with its family. As an educator, if we aim for successful school education, we have to create goals that involve parents, include family education and give it importance. To participate in pre-school education, parents should be informed about the program by the school which should be provided in written form. To provide a beneficial education, first, it is necessary to establish positive communication with the families. Positive communication with families does not happen all at once but can take place at different times in each family. Informing parents through family support programs, providing new skills and counseling for their problems improves the relationship dynamics within the family, and accelerates the development of the child. Pre-school education, is an educational process which is planned and programmed. If the education is aimed to continue at home, while preparing the pre-school education program, not only the child but  the family should be considered within the program as well. For this reason, it was stated that ensuring school-family cooperation is important in terms of developing desired behaviors of the child. To ensure the continued active participation of families in planning and practice, it was also emphasized that families should be constantly informed about what is being done at school.Keywords: preschool, school, family involvement, education.